Reinforcing Students’ Character through Al-Islam and Muhammadiyah Education: A Study of Muhammadiyah Elementary Schools in Medan - Nursakinah; Dewi Juni Artha; Mutia Febriyana (Tsaqila | Jurnal Pendidikan dan Teknologi, 2026)
This study aims to optimize Al-Islam and Muhammadiyah Education (AIK) in strengthening students’ character values at Muhammadiyah Elementary School in Medan City. AIK education plays a strategic role in shaping students’ character in accordance with Islamic values and the Muhammadiyah philosophy, such as integrity, responsibility, independence, and social awareness. This study employs a field research method using a phenomenological approach. Data collection techniques include observation, interviews, document analysis, and documentation. The results indicate that the implementation of structured and relevant AIK education can enhance students’ understanding of Islamic values and foster positive character traits in their daily lives. Optimizing Al-Islam and Kemuhammadiyahan education as an effort to strengthen the character values of students at Muhammadiyah Elementary Schools in the city of Medan has been carried out through various integrations of Al-Islam and Kemuhammadiyahan education, including in the curriculum and learning designed through 1) Al-Islam and Kemuhammadiyahan Subjects (Aqidah, Akhlak, Fiqh, Al-Qur’an, Hadith, and Islamic History as well as the Struggle of Muhammadiyah), 2) Integration of AIK into General Subjects (Mathematics, Science, and Indonesian Language), and 3) Tahfidzh and Tilawah Learning (programs for memorizing and understanding the Qur’an with memorization targets appropriate for lower and upper grade levels). Furthermore, religious activities at school include: 1) Congregational Dhuha and Dhuhr prayers at school, 2) Morning Quran Recitation (students read the Quran together before starting lessons), 3) Ramadan Intensive Islamic Boarding School (a special program during Ramadan to deepen religious knowledge and character education based on Islam and Muhammadiyah principles), and 4) Commemoration of Major Islamic Holidays (activities for the Prophet’s Birthday, Isra’ Mi’raj, the Islamic New Year, and Ramadan with various educational activities). Furthermore, the cultivation of Islamic character is achieved through 1) instilling Islamic etiquette in daily life, 2) the 5S Culture to encourage students to behave courteously, respect teachers and peers, and maintain proper conduct in social interactions, and 3) the ISHA Movement (Infaq and Shadaqah) through activities such as Friday Blessings, Class Infaq, and Social Service. Moreover, the methods employed to optimize Islamic and Muhammadiyah Education at the Muhammadiyah Elementary School in Medan include AIK extracurricular activities such as 1) Tapak Suci, a Muhammadiyah-specific martial art that teaches discipline and resilience, 2) Islamic competitions such as Quran memorization contests, AIK quizzes, calligraphy, and Islamic speeches, 3) Worship Practice, Training, and Cadre Development to foster a spirit of organization from an early age through the Muhammadiyah Student Association (IPM) at the elementary school level.